2013
DOI: 10.1111/resp.12207
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical characteristics and prognostic factors of combined pulmonary fibrosis and emphysema versus idiopathic pulmonary fibrosis alone

Abstract: This study demonstrated that the prognosis of CPFE is significantly worse than that of IPF alone. In particular, CPFE with paraseptal emphysema associated with high esPAP has an extremely poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
4
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 21 publications
3
76
4
6
Order By: Relevance
“…All patients with CPFE were current or ex-smokers (19). Sugino et al reported that the prevalence of LC among patients with CPFE is higher than that in patients with IPF alone (20). CPFE is also observed in patients with CTD-ILD and may be associated with an increased risk of LC (9).…”
Section: Discussionmentioning
confidence: 99%
“…All patients with CPFE were current or ex-smokers (19). Sugino et al reported that the prevalence of LC among patients with CPFE is higher than that in patients with IPF alone (20). CPFE is also observed in patients with CTD-ILD and may be associated with an increased risk of LC (9).…”
Section: Discussionmentioning
confidence: 99%
“…Mejía et al (3) reported that survival of CPFE patients was poorer compared with that of patients with idiopathic pulmonary fibrosis (IPF) alone and that pulmonary hypertension in CPFE patients was an independent predictor of mortality. Previous studies have indicated that CPFE patients have a significantly increased risk of lung cancer compared with patients with chronic obstructive pulmonary disease (COPD) or IPF alone (1,4,5). Post-operative acute exacerbation (AE) of interstitial lung disease in patients with lung cancer is associated with a high mortality rate (43.9%) (6).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of COPD (including emphysema) was reported in 23 studies (online supplementary table S1), of which eight were from Europe [18][19][20][21][22][23][24][25], eight were from North America [6,[26][27][28][29][30][31][32], six were from Asia [33][34][35][36][37][38] and one was from South America (Brazil) [39]. The reported prevalence of COPD ranged from 6% to 67% (figure 2) ( prevalence ranges by country: 12% [21] to 51% [18] in Europe, 8% [26] to 67% [31] in North America and 34% [36] to 65% [34] in Asia).…”
Section: Respiratory Comorbidities Copdmentioning
confidence: 99%